Dosage and Frequency Test of Liquid Organic Fertilizer Banana Hump to Results and Growth of Cauliflower (Brassica Oleraceae L.) - Roeswitawati, Dyah (International Journal of Engineering and Technology, 2019)
Increasing crop production through organic farming is a step to safeguard the environment from contaminating the use of chemicals. The application of organic farming is plant cultivation, one of which uses organic fertilizer. Organic fertilizers are fertilizers derived from organic materials in the form of plant residues and animal / human feces that have undergone a decomposition process so that they can be utilized by plants. Banana humps are one of the organic ingredients which contain microbial decomposers and hormones, so that it can be used as an ingredient in making organic fertilizer. The research was done on December 2014 till February 2015 at UMM experiment station. The research covers dose and application time of organic fertilizer liquid. Organic fertilizer made from banana hump mixed with rice water and molasses by comparison 5 kg : 25 liters : 1 liter then fermented for 3 weeks. Dose of organic fertilizer is 5 ml / plant ;Â 10 ml / plant,Â the frequency of giving organic fertilizer is once a week ; 2 weeks ; 3 weeksÂ and 4 weeks. The results showed that there was an interaction between dose treatment and organic fertilizer applicationÂ on the growth and yield of cauliflower so any changes of organic fertilizer dose will effect to application times and variable growth. Treatment combination dose organic fertilizer 5 ml/plant frequency 3 weeks or 7,5 ml/plant frequency 2 weeks are good treatment so recommended dosage and time of application.Â